Continuous high-frequency pesticide monitoring in a small tile-drained agricultural stream to reveal diel concentration fluctuations in dry periods - la Cecilia, Daniele; Dax, Anne; Ehmann, Heinz; Koster, Margie; Singer, Heinz; Stamm, Christian (Frontiers in Water, 2023)
Plant Protection Products (PPPs) pose a threat to surface water quality worldwide. While small streams compose the majority of the stream lengths and are crucial for biodiversity, their exposure patterns to PPPs and transformation products (TPs) are largely understudied in dry periods. This knowledge gap can lead to ineffective monitoring strategies for addressing water quality issues. Here, we continue the in-depth analysis of a unique continuous high-frequency (20 minutes) dataset for 60 PPPs and TPs in a small tile-drained agricultural stream by focussing on two extended dry periods occurred during a 41-day-long monitoring in 2019. The overall 2560 concentration data per compound obtained with the MS2Field platform revealed: (i) surprisingly high maximum concentrations (hundreds to thousands ng/l for some compounds) over extended periods of time, (ii) novel diel fluctuations of concentrations in the order of hundreds of ng/l for some PPPs and TPs, (iii) unexpected high concentrations (up to 220 ng/l) of a legacy compound (the fungicide oxadixyl withdrawn from the Swiss market in 2005). We hypothesised the cause of our findings was rooted in high PPPs levels in the shallow groundwater. To investigate this, we complemented our measurements with the long-term Swiss national monitoring program integrating samples over 14 days at the same location. The continuous long-term measurements found a few PPPs all year-round, thus indicating the presence of persistent contamination sources in the catchment. Next, we collected spatially distributed grab samples in tile drain outlets and stream water on a dry summer day in 2020. The dry-day campaign not only confirmed our hypothesis given the measured high concentrations of PPPs and TPs in tile drain outlets but also highlighted large spatial variability in measured concentrations along the stream. Hereafter, we highlight the questions that different monitoring schemes can answer in dry conditions. This information was relevant to observe for the first time, and thus foresee, the dynamic patterns of PPPs and TPs in the aquatic ecosystem in dry summer conditions, with the latter generally becoming more frequent due to climate change.